2021
DOI: 10.3389/fnagi.2021.712545
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proteomic Biomarkers Relating to Alzheimer’s Disease: A Meta-Analysis Based on Our Own Studies

Abstract: Background and Objective: Plasma biomarkers for the diagnosis and stratification of Alzheimer’s disease (AD) are intensively sought. However, no plasma markers are well established so far for AD diagnosis. Our group has identified and validated various blood-based proteomic biomarkers relating to AD pathology in multiple cohorts. The study aims to conduct a meta-analysis based on our own studies to systematically assess the diagnostic performance of our previously identified blood biomarkers.Methods: To do thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…[25,26] Insulin resistance plays an important role in the progression of T2DM, which is observed in approximately 80% of the patients with AD. [27] Insulin signaling pathways, including altered levels of insulin and insulin-like growth factor (IGF), are impaired in the brains of AD patients. [28,29] Insulin-related signaling pathways play a key role in energy homeostasis, neuronal survival, and memory processes, all of which are critical for learning and cognitive functions in the cortical and hippocampal areas.…”
Section: Neuronmentioning
confidence: 99%
“…[25,26] Insulin resistance plays an important role in the progression of T2DM, which is observed in approximately 80% of the patients with AD. [27] Insulin signaling pathways, including altered levels of insulin and insulin-like growth factor (IGF), are impaired in the brains of AD patients. [28,29] Insulin-related signaling pathways play a key role in energy homeostasis, neuronal survival, and memory processes, all of which are critical for learning and cognitive functions in the cortical and hippocampal areas.…”
Section: Neuronmentioning
confidence: 99%
“…It is associated to amyloid deposition [ 41 ] and brain atrophy [ 42 ]. The lower levels of this protein in AD compared to FTD and controls [ 43 ] indicate that this marker is specifically associated to AD pathogenesis. Experimental and neuropathological studies indeed suggest that this protein may contribute to AD by altering thrombosis and fibrinolysis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that defining blood component changes, including altered circulating proteins, provides fundamental insights into numerous diseases (Luczak et al, 2015;Cao et al, 2020;Harbaum et al, 2022) and helps to identify clinical biomarkers and potential therapeutic targets (Hoogeveen et al, 2020;Shi et al, 2021). Using human plasma proteomic data, statistical models termed 'clocks' have been developed which accurately predict chronological age (Tanaka et al, 2018;Lehallier et al, 2019).…”
Section: Figurementioning
confidence: 99%